Circuito econômico solidário: transformações territoriais através de práticas de inovação social na sub-região II do departamento de Risaralda-Colômbia - Hoyos, César Andrés Alzate [UNESP] (2016)
In order to understand the collective initiatives that are striving to propose fairer local development, equitable and autonomous, we study from the social innovation, the different socio-spatial practices that configure processes of territorialization in environments of solidarity economy, for which we need to identify and diagnose such practices in organizations that participated in an integration project called here Economic Circuit Solidary; in addition, the instrumentalizing character of social innovation in the construction of territorialities linked to the technical and symbolic action and to understand and explain these territorialities identified in the circuit. In search of a referential and methodological framework that fit the needs of the context and objectives of the research, we adapted the concept of interface to focus the analysis in a relational field that underlined the processuality and multidimensionality of the territory. The result of this process is an understanding, at least approximation, of the territorialities that configure three Solidarity Economic Circuits studied, however, deepening, by its degree of development, a particular one, which allowed to make a dialectical synthesis between theory and empiricism.